Increased blood viscosity and red blood cell aggregation in patients with COVID‐19. Issue 3 (23rd December 2021) - Nader, Elie; Nougier, Christophe; Boisson, Camille; Poutrel, Solene; Catella, Judith; Martin, Fiona; Charvet, Juliette; Girard, Sandrine; Havard‐Guibert, Salomé; Martin, Marie; Rezigue, Hamdi; Desmurs‐Clavel, Helene; et al.
Abstract: The aim of this study was to (1) analyze blood viscosity, red blood cell (RBC) deformability, and aggregation in hospitalized patients with Coronavirus disease 19 (COVID‐19); (2) test the associations between impaired blood rheology and blood coagulation; and (3) test the associations between impaired blood rheology and several indicators of clinical severity. A total of 172 patients with COVID‐19, hospitalized in COVID‐unit of the Internal Medicine Department (Lyon, France) participated in this study between January and May 2021. Clinical parameters were collected for each patient. Routine hematological/biochemical parameters, blood viscosity, RBC deformability and aggregation, and RBC senescence markers were measured on the first day of hospitalization. A control group of 38 healthy individuals was constituted to compare the blood rheological and RBC profile. Rotational thromboelastography was performed in 76 patients to study clot formation dynamics. Our study demonstrated that patients with COVID‐19 had increased blood viscosity despite lower hematocrit than healthy individuals, as well as increased RBC aggregation. In‐vitro experiments demonstrated a strong contribution of plasma fibrinogen in this RBC hyper‐aggregation. RBC aggregation correlated positively with clot firmness, negatively with clot formation time, and positively with the length of hospitalization. Patients with oxygen supplementation had higher RBC aggregation and blood viscosity than those without, and patients with pulmonary lesions had higher RBC aggregation and enhanced coagulation than those without. This study is the first to demonstrate blood hyper‐viscosity and RBC hyper‐aggregation in a large cohort of patients with COVID‐19 and describe associations with enhanced coagulation and clinical outcomes.